The Efficacy and Safety of Reduced-Dose Oral Methylprednisolone in High-Risk Immunoglobulin A Nephropathy - Dana Kim; Jicheng Lv; Michelle Hladunewich; Vivekanand Jha; Lai Seong Hooi; Helen Monaghan; Sana Shan; Heather N. Reich; Sean Barbour; Laurent Billot; Hong Zhang; Vlado Perkovic; et al. (Kidney International Reports)
Introduction: The therapeutic effects of steroids in immunoglobulin A nephropathy (IgAN) global (TESTING) study reported that methylprednisolone reduces the risk of major kidney events in individuals with IgAN at high risk of disease progression compared to supportive care alone but is associated with increased serious adverse events (SAEs) primarily with full-dose therapy. The risk benefit balance of the reduced-dose methylprednisolone regimen is examined in this prespecified analysis of the reduced-dose cohort of the TESTING trial. Methods: Between 2017 and 2019, patients with IgAN, proteinuria ≥1 g/d despite 3 months of renin-angiotensin-system blockade and estimated glomerular filtration rate (eGFR) 30 to 120 ml/min per 1.73 m2 were randomized to reduced-dose methylprednisolone 0.4 mg/kg/d or placebo. The primary outcome was a composite of a 40% eGFR decline, kidney failure, or death due to kidney disease. Results: A total of 241 participants were randomized and followed-up with for a median of 2.5 years (mean age: 37 years; baseline eGFR: 65 ml/min per 1.73 m2; proteinuria: 2.48 g/d). Methylprednisolone was associated with fewer primary outcome events compared to placebo (7/121 vs. 22/120; hazard ratio [HR]: 0.24; 95% confidence interval [CI]: 0.10–0.58, P = 0.002), lowered proteinuria, and reduced eGFR rate of decline from baseline. The mean difference between methylprednisolone and placebo in proteinuria and eGFR from baseline was −1.15 g/d and 7.9 ml/min per 1.73 m2 (P < 0.001) at 12 months, respectively; however, these benefits were lost over time. There were 7 versus 3 SAEs in the methylprednisolone versus placebo group (HR: 1.97; 95% CI: 0.49–7.90), including 5 versus 2 infections. Conclusion: Reduced-dose methylprednisolone is effective in improving kidney outcomes in high risk IgAN; however, it is associated with a modestly higher number of SAEs compared to placebo.